Developing a methodology that incorporates ceramic media properties to model power draw in a M4 IsaMill™ - Durant, Abraham Cristiaan (University of Cape Town, 2015)
Includes abstract. === Includes bibliographical references. === Sustainability in the mineral processing industry is guaranteed by the efficient operation of unit processes to maximize profitability within the prevailing economic conditions at the time. Efficient operation can be measured based on cost, metallurgical and energy efficiency of the operation or as a combination of the three, with energy efficiency becoming increasingly more important in the world and current South African context even more so. With ore bodies becoming more complex and finely disseminated the need for ultra fine grinding to maximise mineral recoveries in PGM concentrating operations by means of mainstream grinding has become more important. Conventional grinding technology was found to be inefficient to address this challenge. Introduction of new stirred milling technology for mainstream grinding using ceramic media successfully addressed the challenge posed by finely disseminated and complex PGM ore bodies. Introduction of new technology also brings about optimisation opportunities on various levels to ensure that the new technology is performing optimally in order to maximise profitability. As relatively new technology, several potential optimisation areas for the horizontal stirred mill has been identified for study. Operating costs for IsaMills™ horizontal mills can be classified into 3 groups i.e. media, maintenance and energy cost. Ceramic media type used can potentially play a role in determining the cost contribution of each of these groups to the overall mill operating costs. An area found very important to study, taking into consideration the enormous strain on the South African electricity supply system, was the impact of ceramic media properties on the energy efficiency of the horizontal stirred mill.